Relation between Arterial Stiffness and Markers of Inflammation and Hemostasis – Data from the Population-based Gutenberg Health Study - Natalie Arnold (Nature Portfolio, 2017)
Abstract The relation between inflammation, hemostasis and arterial stiffness is of pathophysiological relevance for the development of cardiovascular disease (CVD). Data investigating this interplay using stiffness index (SI) by digital photoplethysmography are not available yet. Therefore, sex-specific relation between SI and inflammatory and hemostatic biomarkers was investigated within 13,724 subjects from the population-based Gutenberg Health Study. C-reactive protein (CRP), white blood cell count (WBCC), neopterin, interleukin-18, interleukin-1 receptor antagonist (IL-1RA), fibrinogen and hematocrit were measured. Multivariable linear regression analysis with adjustment for cardiovascular risk factors, medication, and hormonal status (in females) revealed an independent association between SI and WBCC, IL-1RA and hematocrit in both sexes, and with fibrinogen in women. There was a joint effect of increasing tertiles of SI and biomarker concentrations for future CVD risk prediction. Subjects with both SI and biomarker concentration above the median had the worst overall survival and with both below the median the best survival during a follow-up period of 6.2 ± 1.7 years, except for hematocrit. The results support the relation between inflammation, hemostasis and arterial stiffness measured by digital photoplethysmography. Markers of inflammation and hemostasis modulate the ability of SI to identify subjects at risk for future CVD or higher mortality.